Dual wavelength erbium-doped fiber laser using a tapered fiber - Harun, Sulaiman Wadi; Lim, Kok Sing; Jasim, Ali Abdulhadi; Ahmad, Harith (Taylor & Francis, 2010)
A tapered fiber is fabricated by heating and stretching a piece of optical fiber after the polymer protective cladding has been removed. An equidistant comb-like transmission spectrum, with a spacing of 1.6 nm and an extinction ratio of more than 5 dB, was obtained by the tapered fiber due to the multibeam interferences of the cladding modes. The tapered fiber was applied in a ring erbium-doped fiber laser (EDFL) to generate dual-wavelength lasing oscillations. The EDFL operates at wavelengths of 1557.0 nm and 1558.6 nm with a stable peak power and a signal-to-noise ratio of more than 40 dB.